Second direct-acting antiviral therapy for hepatitis C virus infection after umbilical cord blood transplantation: A case report. Issue 8 (August 2021) - Onodera, Koichi; Onishi, Yasushi; Inoue, Jun; Tanaka, Yuya; Yonha, Lee; Ichikawa, Satoshi; Fukuhara, Noriko; Yokoyama, Hisayuki; Murai, Kazunori; Masamune, Atsushi; Harigae, Hideo
Abstract: Hepatitis C virus (HCV) infection has an adverse impact on outcomes after allogeneic hematopoietic stem cell transplantation (HSCT). It is recommended that HSCT candidates infected with HCV receive the treatment prior to transplantation. Although the recent approval of direct-acting antivirals (DAAs) has led to great advances in the treatment of HCV infection, little information is available on the efficacy and safety of DAA therapy in patients receiving allogeneic HSCT. Herein, we report the clinical course of an umbilical cord blood (UCB) recipient treated with DAAs for HCV infection. The patient achieved HCV RNA negativity with glecaprevir and pibrentasvir after consolidation therapy for acute myeloid leukemia (AML), and underwent transplantation before confirming sustained virological response (SVR) at 12 weeks. The HCV viral load became detectable on day +28 after transplantation and second HCV treatment with sofosbuvir, velpatasvir, and ribavirin was required. It is important to confirm SVR prior to transplantation, but it is often difficult. If early transplantation is required, close monitoring of HCV RNA after transplantation is needed. Further investigation is required to clarify the optimal management of HCV infection for allogeneic HSCT recipients in the DAA era.